Correction of Severe Myelofibrosis, Impaired Platelet Functions and Abnormalities in a Patient with Gray Platelet Syndrome Successfully Treated by Stem Cell Transplantation. (18th May 2020) - Favier, Rémi; Roussel, Xavier; Audia, Sylvain; Bordet, Jean Claude; De Maistre, Emmanuel; Hirsch, Pierre; Neuhart, Anne; Bedgedjian, Isabelle; Gkalea, Vasiliki; Favier, Marie; Daguindau, Etienne; Nurden, Paquita; et al.
Abstract: Gray platelet syndrome (GPS) is an inherited disorder. Patients harboring GPS have thrombocytopenia with large platelets lacking α-granules. A long-term complication is myelofibrosis with pancytopenia. Hematopoietic stem cell transplant (HSCT) could be a curative treatment. We report a male GPS patient with severe pancytopenia, splenomegaly and a secondary myelofibrosis needing red blood cells transfusion. He received an HSCT from a 10/10 matched HLA-unrelated donor after a myeloablative conditioning regimen. Transfusion independence occurred at day+21, with a documented neutrophil engraftment. At day+ 180, we added ruxolitinib to cyclosporine and steroids for a moderate chronic graft versus host disease (GVHD) and persistent splenomegaly. At day+240 GVHD was controlled and splenomegaly reduced. Complete donor chimesrism was documented in blood and marrow and platelets functions and morphology normalized. At day+ 720, the spleen size normalized and there was no evidence of marrow fibrosis on the biopsy. In GPS, HSCT may be a curative treatment in selected patients with pancytopenia and myelofibrosis.